2021
DOI: 10.1101/2021.09.06.459160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expectations boost the reconstruction of auditory features from electrophysiological responses to noisy speech

Abstract: Online speech processing imposes significant computational demands on the listening brain. Predictive coding provides an elegant account of the way this challenge is met through the exploitation of prior knowledge. While such accounts have accrued considerable evidence at the sublexical- and word-levels, relatively little is known about the predictive mechanisms that support sentence-level processing. Here, we exploit the 'pop-out' phenomenon (i.e. dramatic improvement in the intelligibility of degraded speech… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 147 publications
(221 reference statements)
0
2
0
Order By: Relevance
“…De-identified raw and preprocessed data are openly available on the Open Science Framework platform: https://osf.io/5qxds ( Corcoran et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…De-identified raw and preprocessed data are openly available on the Open Science Framework platform: https://osf.io/5qxds ( Corcoran et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a considerable proportion of work examining the oscillatory correlates of higher-order language processing have not explicitly accounted for modulations in broadband aperiodic activity (e.g., Bonhage et al, 2017; Corcoran et al, 2022; Kepinska et al, 2017; Lewis et al, 2016; Mai, Minett, & Wang, 2016; Prat et al, 2016; Rossi & Prystauka, 2020; c.f., Cao et al, 2022), making it difficult to determine whether oscillatory activity parsimoniously explains behavioural outcomes. By separating oscillatory and aperiodic components, we have demonstrated that the aperiodic exponent flattens across time, while, for example, theta and alpha power increase across time throughout the language learning phase.…”
Section: Discussionmentioning
confidence: 99%